2006
DOI: 10.1111/j.1442-9993.2006.01583.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of supplementary foods by Australian magpies Gymnorhina tibicen: Implications for wildlife feeding in suburban environments

Abstract: The provision of foods to wild birds is an extremely common practice among householders throughout the Western world. Nonetheless, concerns over potential impacts of the practice are currently being raised, including the possibility that some species may become reliant on human-provided food. We compared the foraging and breeding ecology of pairs of fed and unfed Australian magpies Gymnorhina tibicen living in suburban environments in Brisbane, Queensland, Australia. Detailed behavioural observations of both f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 19 publications
0
44
0
3
Order By: Relevance
“…These include the spread of disease, nutritional imbalances, enhancement of introduced or unpopular species, increased aggression, the creation of 'ecological traps', increases in unpopular species, including vermin, and, most frequently mentioned, the possibility of dependency on anthropogenic foods (Anderson et al 1997;O'Leary and Jones 2006). (Only some of these concerns are further discussed here; see Orams 2002, Ishigame et al 2006 for further discussion.)…”
Section: Should We Be Worried?mentioning
confidence: 99%
See 1 more Smart Citation
“…These include the spread of disease, nutritional imbalances, enhancement of introduced or unpopular species, increased aggression, the creation of 'ecological traps', increases in unpopular species, including vermin, and, most frequently mentioned, the possibility of dependency on anthropogenic foods (Anderson et al 1997;O'Leary and Jones 2006). (Only some of these concerns are further discussed here; see Orams 2002, Ishigame et al 2006 for further discussion.)…”
Section: Should We Be Worried?mentioning
confidence: 99%
“…Toms 2003). However, several recent studies looking specifically at this issue have found that a variety of species (including suburban Australian Magpies, British tits and Scrub Jays (Aphelocoma coerulescens) (Cowie and Hinsley 1988;Fleischer et al 2003;O'Leary and Jones 2006)), all with easy access to anthropogenic foods, used only small proportions of this food, but especially so when feeding their chicks. Most impressive of all, a population of North American Black-capped Chickadees (Poecile atricapillus) studied over several harsh winters in Maine showed no dependency on feeders and survived even when the feeders were suddenly withdrawn (Brittingham and Temple 1992).…”
Section: Feeding Really Does Change Thingsmentioning
confidence: 99%
“…As well as differences in avian community composition at feeders of Northern and Southern Hemispheres (Table 1), there are major differences in the types of food supplements provided, especially in Australia where meat is routinely fed to populous species such as Australian magpies, butcherbirds Cracticus spp., and kookaburras (Alcedinidae) that are all relatively large species and abundant in urban landscapes (O'Leary and Jones, 2006;Jones, 2011). The most commonly provisioned form of meat is raw beef mince (or ground beef), presumably because it is relatively inexpensive and readily available, although pieces of sausage, salami, ham, bacon, and cooked chicken are also provided (Ishigame and Baxter, 2007).…”
Section: North Vs Southmentioning
confidence: 99%
“…In their study of wintering black-capped chickadees in Wisconsin in the US, Brittingham and Temple (1992) found that a population supplied with supplementary food for 25 years had an identical survivorship to that of an unfed (control) population nearby. In Australia, adult Australian magpies continued to provide natural foods to their nestlings even when large supplies of favored foods were readily available (O'Leary and Jones, 2006). There are numerous other studies from a wide variety of species that strongly suggest that in the vast majority of cases individuals that visit feeders do so in rather a sporadic fashion with the diet comprising mainly natural food sources (e.g., Harrison, 2010;Robb et al, 2011;but see Sauter et al, 2006).…”
Section: Feeding and Dependencymentioning
confidence: 99%
See 1 more Smart Citation